Conference Companion on Human Factors in Computing Systems - CHI '95 1995
DOI: 10.1145/223355.223691
|View full text |Cite
|
Sign up to set email alerts
|

Pointing on a computer display

Abstract: Four experiments were performed to study planning and control of pointing movements in human-computer interaction (HCI). We examined how theories and models derived from motor controI research on natural movements apply to HCI, in order to understand why mediated pointing is difficult, and to suggest strategies for improvinginterfaces. An OPTOTRAK sensor and computer system mapped 3-D hand movements to a 2-D display with less than 25 ms lag. Subjects viewed targets on a graphics display and showed evidence for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 191 publications
0
37
0
1
Order By: Relevance
“…Previous studies have found that superimposed displays are an ideal way to facilitate performance in remote environments [3,7,8,16]. The results of experiment 2 indicate that the superimposed viewing condition also facilitates motor planning, shortening the decision-making process.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Previous studies have found that superimposed displays are an ideal way to facilitate performance in remote environments [3,7,8,16]. The results of experiment 2 indicate that the superimposed viewing condition also facilitates motor planning, shortening the decision-making process.…”
Section: Discussionmentioning
confidence: 72%
“…The benefits of placing a superimposed image over the work plane on task performance have been documented in both virtual and endoscopic task environments [7,8,16]. Experiment 2 extended these benefits to motor planning, which takes place even before the actual movement is initiated.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Fitts's Law [20,15] predicts movement time based on a user's movements in motor space, not on the distance traveled by the cursor. Although we can assume that switching attention between displays during targeting has a time cost, is this reflected in a slower ballistic movement or a lengthening of the homing-in phase?…”
Section: Q3 (What Is the Relationship Between Gap And Completion Timementioning
confidence: 99%
“…Esta relação foi inicialmente modelada por Fitts (1954), que demonstrou que o tempo de movimento em tais tarefas é uma função linear do logaritmo do dobro da amplitude de movimento dividida pela largura do alvo. Esta proposição, a qual veio a ser conhecida como Lei de Fitts, tem recebido amplo suporte empírico em diferentes tipos de tarefa envolvendo velocidade e precisão de movimento, tais como contatar um alvo físico com a mão ou estilete (Fitts, 1954;Fitts & Peterson, 1964;MacKenzie, Marteniuk, Dugas, Liske & Eickmeier, 1987;Marteniuk, MacKenzie, Jeannerod, Athenes & Dugas, 1987), movimentos de contatação feitos com a cabeça (Andres & Hartung, 1989), atingir um alvo em monitor de computador através de movimentos com um mouse (Graham, 1996), e em tarefas de agarrar objetos (Bootsma, Marteniuk, MacKenzie & Zaal, 1994). A explicação que tem sido dada para esse fenômeno é que o aumento do índice de dificuldade, particularmente pela diminuição da largura do alvo, gera uma maior demanda de processamento de "feedback" em função da maior restrição espacial colocada pela tarefa, fazendo com que o tempo de movimento seja aumentado como conseqüência do maior número de ajustes necessários para obtenção de sucesso.…”
unclassified